Perlindungan Hukum Terhadap Anak Sebagai Pelaku Tindak Pidana Mucikari Prostitusi Online - Adyatama, Bagus Prayoga Anggun; Surahman, Surahman (PATTIMURA Legal Journal, 2024)
Introduction: Child legal protection analyzed from the object of study, namely Law Number 11 of 2012 concerning the Juvenile Criminal Justice System. Purposes of the Research: Revealing the juvenile justice procedures in dealing with criminal cases of online prostitution pimping by minors based on the judge's considerations in deciding the case by imposing prison sanctions on children in Decision Number 4/Pid.Sus-Anak/2023/PN Tgt. Methods of the Research: This research is normative legal research with document study data collection techniques that examine various documents related to the research object. The data used in this research are primary legal material sources and secondary legal material sources. Results Originality of the Research: The research results found that in the provisions of Judge's Decision No. 4/Pid.Sus- Anak/2023/PN Tgt., there are several provisions related to juvenile justice that are not in accordance with the Juvenile Criminal Justice System Law and Islamic Law. In decision making, there are still several things that are not appropriate, especially in prison sentences imposed on child perpetrators. Judges need to review several aspects in issuing decisions regarding this matter so that it does not cause negative impacts in the future.